Data Management in Special Education Research Scientific Review - Allala, Saep Kamel; Abushaira, Mohamed; Obaid, Mahmoud Sameer Faris; Almalak, Ashraf Ibrahim Suliman (Journal of Cultural Analysis and Social Change, 2025)
Data management is defined as: The process of understanding, collecting, storing, organizing, and maintaining data that has been created, collected, stored, organized, and maintained. Data management is an important aspect of scientific research in special education. Effective data management is an important process in providing analytical information to help drive decision-making by those responsible for special education. In this paper, data management in special education will be highlighted in the following areas: The importance of collecting accurate and reliable data, using appropriate analysis methods, avoiding bias against people with disabilities, the need for appropriate data management strategies, and the challenges associated with data management in special education research. In the end, the paper concludes with a number of recommendations, including adopting specific and clear strategies in data management in special education research, establishing local and Arab centers for special education data management, training researchers in the field of data management, and introducing it into postgraduate courses.